2018
DOI: 10.1042/bsr20171615
|View full text |Cite|
|
Sign up to set email alerts
|

Up-regulation of microRNA-340 promotes osteosarcoma cell apoptosis while suppressing proliferation, migration, and invasion by inactivating the CTNNB1-mediated Notch signaling pathway

Abstract: Osteosarcoma (OS) is the most common histological form of primary bone cancer. It is most prevalent in teenagers and young adults. The present study aims at exploring the regulatory effect of microRNA-340 (miR-340) on OS cell proliferation, invasion, migration, and apoptosis via regulating the Notch signaling pathway by targeting β-catenin (cadherin-associated protein) 1 (CTNNB1). OS tissues belonging to 45 patients and normal femoral head tissues of 45 amputees were selected. Cells were allocated to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…For example, miR-340-5p could negatively regulate Wnt/ β-catenin signaling pathway through targeting STAT3 gene, thereby inhibiting the development of osteosarcoma [65] . Meanwhile, overexpression of miR-340-5p could down-regulate the CTNNB1-mediated Notch signaling pathway, thereby suppressing osteosarcoma migration and invasion [66] . However, the regulatory relationships between miR-340-5p and these hub genes in patients with lung metastasis of osteosarcoma need to be con rmed by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-340-5p could negatively regulate Wnt/ β-catenin signaling pathway through targeting STAT3 gene, thereby inhibiting the development of osteosarcoma [65] . Meanwhile, overexpression of miR-340-5p could down-regulate the CTNNB1-mediated Notch signaling pathway, thereby suppressing osteosarcoma migration and invasion [66] . However, the regulatory relationships between miR-340-5p and these hub genes in patients with lung metastasis of osteosarcoma need to be con rmed by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-340 was shown to be a potential therapeutic agent for GBM via its inhibitory effects on Bcl-w-induced platelet-derived growth factor-A (PDGF-A) and Sox2 activation 53 . A recent study revealed that miR-340 could suppress osteosarcoma (OS) cell proliferation by inactivating the Notch signaling pathway by down-regulating CTNNB1 54 . It has been reported that the overexpression of miR-340 inhibited human esophageal squamous cell carcinoma (ESCC) cell growth by modulating the expression of phosphoserine aminotransferase 1 ( PSAT1 ), and it may contribute to the progression of ESCC 55 .…”
Section: Functional Roles Of Mir-340 In Cancersmentioning
confidence: 99%
“…At present, miRNAs dysregulation is an area of great interest when investigating the molecular mechanisms of renal tumorigenesis (30). Numerous studies reported that miRNAs serve crucial roles in the regulation of various cellular processes, including cell cycle control, proliferation, migration and apoptosis (31,32). Furthermore, aberrant miRNA expression has been associated with a wide range of human diseases, including cancer (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%